Unrecognized diversity of Trocheta species (Hirudinea: Erpobdellidae): resolving a century-old taxonomic problem in Crimean leeches. Issue 2 (17th February 2020) - Khomenko, Andrii; Utevsky, Serge; Utevsky, Andriy; Trontelj, Peter
Abstract : Erpobdellid leeches of the genus Trocheta are among the biggest and most charismatic members of their class. The studies of the group have a long and complicated history due to the lack of reliable distinguishing features, which impedes the taxonomy of the genus. A number of Trocheta species have been misclassified for years if not centuries. Our present research demonstrates that the genus Trocheta is characterized by high cryptic diversity since some populations that have been viewed as the same species should be, in fact, assigned to different species. Trocheta leeches from the Dniester basin and the Crimean Peninsula have been both confused with each other and erroneously assigned to species that do not occur in southern Ukraine. Here, a new species from the Crimean Peninsula, Trocheta blanchardi sp. nov., is described based on a phylogenetic analysis of cox1 gene sequences and a reassessment of morphological characters such as colouration, annulation, size and arrangement of papillae, and genital anatomy. The analysis suggests close relationships of T. blanchardi sp. nov. to Anatolian species. Given its fragile habitats and restricted range, the species needs serious protection and further surveys. Obviously, more species await description as is evident from the significant genetic differences between leech populations. http://zoobank.org/urn:lsid:zoobank.org:pub:8610460D-862B-4F28-8520-5C8D11AEB015